2021
DOI: 10.1038/s41396-021-01064-z
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-oxidizing archaea possess a wide range of cellular ammonia affinities

Abstract: Nitrification, the oxidation of ammonia to nitrate, is an essential process in the biogeochemical nitrogen cycle. The first step of nitrification, ammonia oxidation, is performed by three, often co-occurring guilds of chemolithoautotrophs: ammonia-oxidizing bacteria (AOB), archaea (AOA), and complete ammonia oxidizers (comammox). Substrate kinetics are considered to be a major niche-differentiating factor between these guilds, but few AOA strains have been kinetically characterized. Here, the ammonia oxidation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 92 publications
4
80
0
1
Order By: Relevance
“…In fact, ammonium concentration was the variable that better explained the Nitrospira distribution in the studied waterworks. Although little is known about the range of ammonia affinities in comammox Nitrospira , as this trait has only been measured in two species ( 24 , 25 ), other ammonia oxidizers have ammonia affinities spanning several orders of magnitude ( 26 ). Likewise, canonical Nitrospira species affiliated with different lineages have shown niche differentiation based on nitrite concentration ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, ammonium concentration was the variable that better explained the Nitrospira distribution in the studied waterworks. Although little is known about the range of ammonia affinities in comammox Nitrospira , as this trait has only been measured in two species ( 24 , 25 ), other ammonia oxidizers have ammonia affinities spanning several orders of magnitude ( 26 ). Likewise, canonical Nitrospira species affiliated with different lineages have shown niche differentiation based on nitrite concentration ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation might be that the co-occurrent comammox Nitrospira species had different ammonia affinities, and they would occupy different sites in the highly porous filter material (23). So far, little is known about the variability of ammonia affinity in comammox Nitrospira as this feature has only been reported for two comammox species (24,25), however, a wide range of ammonia affinities have been observed in other ammonia oxidizers (26). Another reason could lie in the abundance of unique genes in each comammox Nitrospira species (> 250 in average ( 21)).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrosoarchaeum koreensis (10 mM L –1 ), and a strain in the AOA AC2 enrichment culture (5 mM L –1 ) ( French et al, 2012 ). It was found that group I.1b AOA species could tolerate very high ammonium concentrations ( Jung et al, 2021 ).…”
Section: Opportunity For Nitrogen Removal By Ammonia-oxidizing Archaea and Anaerobic Ammonia-oxidizing Bacteria In Aquaculture Pondsmentioning
confidence: 99%
“…The latest research also showed that the AOA of group I.1a and group I.1b had a wide range of cellular ammonia affinities ( Jung et al, 2021 ). Group I.1a AOA displayed a high substrate affinity, and the ammonia apparent-half-saturation concentration Km(app), which ranged from ∼2.2 to 24.8 nM, can adapt to oligotrophic conditions, while several group I.1b species possess a wide range of affinities for NH 3 [Km(app) = ∼0.14 to 31.5 μM] ( Jung et al, 2021 ). Compared with AOB, AOA may not have the advantage of using high-concentration ammonia.…”
Section: Opportunity For Nitrogen Removal By Ammonia-oxidizing Archaea and Anaerobic Ammonia-oxidizing Bacteria In Aquaculture Pondsmentioning
confidence: 99%